Enhancing Cyber Psychology Literacy in the Digital Age through a Service Learning Approach for Students in India - Madanu, Pavithra; Reddy, G. Kavitha; B.J. Anitha (PT Agung Media Publisher, 2024)
The digital age has significantly impacted human behavior and mental health, necessitating a deeper understanding of cyber psychology. However, cyber psychology literacy remains low among students in India, despite increasing internet penetration. Addressing this gap, the study implements a Service Learning (SL) approach to enhance students' knowledge of cyber psychology concepts and their practical application. The study engaged university students in a structured SL program comprising classroom-based theoretical instruction and community-based workshops. Quantitative pre- and post-program surveys assessed changes in students' knowledge and attitudes, while qualitative feedback provided insights into the program's impact. The findings showed a 45% increase in students' cyber psychology literacy, with statistical significance (p < 0.01). Key areas of improvement included online identity, cyberbullying prevention, and digital well-being. Qualitative feedback highlighted enhanced student confidence, improved teamwork, and leadership skills, as well as the program’s positive impact on community members. Community workshops increased awareness of digital challenges and practical strategies, with reciprocal benefits for students and the community. The study demonstrated that a Service Learning approach effectively bridges academic knowledge and practical applications, empowering students to address digital challenges and fostering community development. Identified challenges included initial student difficulties in public speaking and low community participation in some workshops, highlighting the need for improved training and outreach strategies. Service Learning is a promising pedagogical approach to enhance cyber psychology literacy among students while fostering societal impact. Future programs should address challenges identified in this study to maximize outcomes and scalability, with potential for broader application in digital mental health education.